Prevalence of Influenza A (H1N1) Seropositivity in Unvaccinated Healthcare Workers in Scotland at the Height of the Global Pandemic. (3rd October 2011) - Smith, Kate; Warner, Pamela; Williams, Linda J.; Adamson, Walt E.; Katikireddi, S. Vittal; Dewart, Paul; Carman, William F.; Templeton, Kate; Denison, Fiona C.; Mackenzie, D. Graham
Abstract : Background . We set out to identify the level of previous exposure to influenza A (H1N1) in unvaccinated healthcare workers (HCWs) at the peak of the pandemic outbreak in the UK, with control samples collected prior to the outbreak. Methods . Cross-sectional study (seroprevalence assessed before and at pandemic peak, with questionnaire data collected at peak of outbreak) in HCWs in Scotland. Results . The prevalence of seropositivity in 493 HCWs at pandemic peak was 10.3%, which was higher than the prepandemic level by 3.7 percentage points (95% CI 0.3% to 7.3%, P = 0.048 ). Seropositivity rates for frontline and nonfrontline HCWs were similar. Conclusion . At pandemic peak, only 10.3% of HCWs were seropositive for influenza A (H1N1), so the great majority were still susceptible to infection at the introduction of the vaccination programme. Few studies have reported on seroprevalence in unvaccinated and asymptomatic participants, so our findings may have relevance to the wider population.